Electron linear accelerator system for natural rubber vulcanization - Rimjaem S. (2017)
© 2016 Elsevier B.V. Development of an electron accelerator system, beam diagnostic instruments, an irradiation apparatus and electron beam processing methodology for natural rubber vulcanization is underway at the Plasma and Beam Physics Research Facility, Chiang Mai University, Thailand. The project is carried out with the aims to improve the qualities of natural rubber products. The system consists of a DC thermionic electron gun, 5-cell standing-wave radio-frequency (RF) linear accelerator (linac) with side-coupling cavities and an electron beam irradiation apparatus. This system is used to produce electron beams with an adjustable energy between 0.5 and 4 MeV and a pulse current of 10–100 mA at a pulse repetition rate of 20–400 Hz. An average absorbed dose between 160 and 640 Gy is expected to be archived for 4 MeV electron beam when the accelerator is operated at 400 Hz. The research activities focus firstly on assembling of the accelerator system, study on accelerator properties and electron beam dynamic simulations. The resonant frequency of the RF linac in π/2 operating mode is 2996.82 MHz for the operating temperature of 35 °C. The beam dynamic simulations were conducted by using the code ASTRA. Simulation results suggest that electron beams with an average energy of 4.002 MeV can be obtained when the linac accelerating gradient is 41.7 MV/m. The rms transverse beam size and normalized rms transverse emittance at the linac exit are 0.91 mm and 10.48 π mm·mrad, respectively. This information can then be used as the input data for Monte Carlo simulations to estimate the electron beam penetration depth and dose distribution in the natural rubber latex. The study results from this research will be used to define optimal conditions for natural rubber vulcanization with different electron beam energies and doses. This is very useful for development of future practical industrial accelerator units.